Redefinition /redirection and incremental change: A systematic review of innovation in teacher education research. (January 2023) - Ellis, Viv; Correia, Catarina; Turvey, Keith; Childs, Ann; Andon, Nick; Harrison, Christine; Jones, Jane; Hayati, Nur
Abstract: This systematic literature review shows how innovation is used within teacher education research; how conceptualised; and whether different types of innovation can be distinguished. 156 studies met the selection criteria. Analysis comprised: frequency of use; research design; and type of innovation, adapting Sternberg et al.'s (2003) typology. Demonstrating that the use of innovation is an increasing, international phenomenon in the field, predominant types of innovation are identified – creative contributions towards new directions and others representing incremental change. However, innovation is often left un-theorised. We suggest that, without theorisation, such studies may have limited value in developing practice and policy.